Commercialication of value added oat ingredients - Patajoki, Markku (MTT, 2004)
Commercialisation of new value added oat ingredients is difficult and time consuming due to competitive circumstances and industry structure. It covers comprehension and incorporation of the benefits of ingredient to consumer needs and ability to enhance teamwork to speed the development phase. As a result the commercialisation period can be reduced and launch success improved.
Keywords: Ka; products; innovation; industry; markets; consumers; commercialication; applications